Functional abuse as a normative and evidentiary weakness that makes it impossible to prosecute the crime of illicit enrichment (SCIÉNDO INGENIUM, 2022)
It was investigated why the classification of the crime of illicit enrichment in article 401 of the Penal Code, in the extreme that functional abuse is understood as a causal link, makes its prosecution and evidentiary activity difficult. To contrast the research hypothesis, a sample of 06 relevant judgments issued by the Supreme Court in the period 2014-2019 was considered; for 03 relevant cases investigated by the Prosecutor's Office on the crime under study; and, as a complement, a personal sample of 15 prosecutors from the penal area of ​​the Santa Fiscal District. The data obtained with the techniques of documentary analysis and the survey were organized and statistically processed for presentation in frequency tables and their discussion with the general and particular methods of science. It was concluded that functional abuse presents a legislative imprecision, which makes it difficult to objectively impute the crime of illicit enrichment, due to the various interpretations made by the Supreme Court and national doctrine, at the same time that it hinders the evidentiary activity, which as a whole is almost null its application for its sanction, in the Fiscal District of Santa
Keywords: Public function; Civil servant; Crime of illicit enrichment; Functional abuse